Occurrence of Psychiatric Disorders, Self-Sufficiency Problems and Adverse Childhood Experiences in a Population Suspected of Violent Extremism - Grimbergen, Christel; Fassaert, Thijs (Frontiers in Psychiatry, 2022)
Background Public health-inspired programs for Countering Violent Extremism (CVE) have developed internationally in a relatively short period of time. Research into these programs is scarce. There is a need for information that helps drive public health interventions. Objectives To present data on the occurrence of psychiatric disorders, self-sufficiency problems and adverse childhood experiences (ACE) in a population suspected of violent extremism. Methods A cross-sectional study, with data from screening reports for 34 adult subjects included in a multi-agency case-based approach on violent extremism in Amsterdam, the Netherlands. Subjects were screened in the period between December 2015 to May 2021. Screening reports, which included the Screener for Intelligence and Learning Disabilities (SCIL) and the Dutch version of the Self-sufficiency Matrix (SSM-D), were used to gather information on the main outcome measures. Results Major psychiatric disease categories were found to be mood and anxiety disorders and mild intellectual disability (each 29.4%), substance related disorders (35.3%), personality disorders (41.2%), and psychotic disorders (14.7%). Complex self-sufficiency problems, measured by the number of people who had self-sufficiency problems in 4+ domains and the number of people who had similar self-sufficiency problems as homeless people in Amsterdam, were found in 35.3 and 32.4% of the client sample. The most prevalent ACE were emotional neglect (47.1%), household mental illness (44.1%), and loss of a parent (38.2%), 35.3% had been exposed to 4+ ACE. An association was found between NACE and self-sufficiency problems on two domains, namely “Mental Health” (rho = 0.51, p = 0.002) and “Law and order” (rho = 0.42, p = 0.013). Conclusions An accumulation of social and psychiatric problems in people suspected of violent extremism underlines the importance of professionals in health and social care being actively involved in developing CVE approaches.